Genetic damage in patients moving from hemodialysis to online hemodiafiltration. (18th August 2015) - Rodríguez-Ribera, Lara; Pastor, Susana; Corredor, Zuray; Silva, Irene; Diaz, Juan Manuel; Ballarin, José; Marcos, Ricardo; Coll, Elisabeth
Abstract : End-stage renal failure patients exhibit a high incidence of genetic damage and genomic instability. Part of this genetic damage is assumed to be caused by the hemodialysis (HD) procedure. To reduce these effects, different alternative HD procedures have been proposed, such as the use of high efficiency convective therapies to improve the reactive oxygen species/antioxidant ratio. To determine the efficiency of online hemodiafiltration (HDF) technique on the levels of DNA damage, we have measured the frequency of micronucleus in peripheral blood lymphocytes of 33 individuals moving from low-flux HD to post-dilution online HDF. In addition to basal levels of genetic damage, potential changes in radiosensitivity were measured as indicators of genomic instability. Plasma antioxidant capacity was also determined. Second samples were obtained after 6 months on the HDF protocol. Results indicate that moving to online HDF therapy produce a significant reduction of the basal levels of genetic damage, but does not affect the genomic instability status. In addition, a greater increase in plasma antioxidant capacity was observed. In spite of the lack of correlation between these parameters, our results confirm the usefulness of the online HDF technique as a way to reduce DNA damage in HD patients.